Tata Kelola Arsip dalam Meningkatkan Efektivitas Administrasi Sekolah di Sekolah Menengah Pertama (SMP) IT Al-Markazul Islami Lhokseumawe - Siregar, Padila (Islamic Education, 2024)
The purpose of this study was to determine how archive management improves the effectiveness of school administration at SMP IT Al-Markazul Islami Lhokseumawe. In addition, to determine the obstacles to archive management in improving the effectiveness of school administration at SMP IT Al-Markazul Islami Lhokseumawe. The method used is a qualitative method with a descriptive approach. The data sources for this study consisted of 3 people at SMP IT Al-Markazul Islami Lhokseumawe, namely the Head of Administration and the two Administrative Staff. The data collection technique here uses observation, interview and documentation techniques. Data analysis is carried out by means of data reduction, data presentation and drawing conclusions. The results of the study indicate that 1) archive management in improving the effectiveness of school administration is carried out through 5 stages; creation stage, management stage, use stage, maintenance stage and destruction stage. 2) there are three obstacles to archive management in improving the effectiveness of school administration, namely; facilities and infrastructure, human resources and school administration services. This study shows that archive management in improving the effectiveness of school administration at SMP IT Al-Markazul Islami Lhokseumawe has been implemented well and based on established principles, but everything is not free from obstacles in its archive management.